Declining Fertility in East Germany After Unification: A Demographic Response to Socioeconomic Change - James C. Witte; Gert G. Wagner (Population and Development Review, 1995)
This investigation draws on detailed, longitudinal sample survey data to examine declining fertility in East Germany. Since the unification of Germany in 1990, the fertility rate in East Germany has been halved-falling well below that of West Germany, which was already among the lowest in the world. The authors assess the manner in which these changes in individual behavior can best be understood as responses to socioeconomic change. They advocate using a broad sociological perspective to view demographic trends-as well as other behavioral and attitudinal changes accompanying unification-as separate, but related, threads in an overall process of assimilation.
Keywords: 330; Fruchtbarkeit; Familienökonomik; Weibliche Arbeitskräfte; Deutschland